Review of the genus Loxocephala Schaum, 1850 (Hemiptera: Fulgoromorpha: Eurybrachidae) with description of three new species from China - Wang, Menglin; Wang, Yinglun (Zootaxa, 2013)
The genus Loxocephala Schaum, 1850 is reviewed. Three new species: L. rugosa sp. nov., L. verticalis sp. nov. and L. mangkangensis sp. nov. are described from China. L. perpunctata Jacobi, 1944 and L. sinica Chou & Huang, 1985 are given supplementary descriptions. In addition, according to the male genitalia, L. sinica sichuanensis Chou & Huang, 1985 is upgraded to species level: L. sichuanensis Chou & Huang, 1985 stat. nov. A key to all the known species of the genus is provided.